(untitled) (European Journal of Marketing and Economics, 2023)
The aim of this paper is to answer the question of whether the practice of small and medium enterprises ( SMEs) in Serbia represents the specifics of human resource management (HRM) in this type of enterprise. The paper contains the practice analysis of the human resource management as a precondition for creating competitive advantage of small an dmedium-sized enterprises in Serbia. The paper methodology is based on appropriate empirical research using a questionnaire, where the results were analyzed by the appropriate statistical method. The paper contains original research criteria in the process HRM in SMEs compared to large enterprises in a transition country that has not joined the EU. The research contributes to confirm the theoretical assumptions about the characteristics of HRM in SMEs and could have practical implications for the search for better professional solutions within the specific characteristics of SMEs. This paper presents only a part of the obtained results, which is the most important for the elaboration of the subject of this paper.